Effects of complex training on explosive strength in adolescent male basketball players - Santos, E. J.; Janeira, M. A. (The Journal of Strength and Conditioning Research, 2008)
The purpose of this study was to evaluate the effects of a complex training program, a combined practice of weight training and plyometrics, on explosive strength development of young basketball players. Twenty-five young male athletes, aged 14-15 years old, were assessed using squat jump (SJ), countermovement jump (CMJ), Abalakov test (ABA), depth jump (DJ), mechanical power (MP), and medicine ball throw (MBT), before and after a 10-week in-season training program. Both the control group (CG; n = 10) and the experimental group (EG; n = 15) kept up their regular sports practice; additionally, the EG performed 2 sessions per week of a complex training program. The EG significantly improved in the SJ, CMJ, ABA, and MBT values (p < 0.05). The CG significantly decreased the values (p < 0.05) of CMJ, ABA, and MP, while significantly increasing the MBT values (p < 0.05). Our results support the use of complex training to improve the upper and lower body explosivity levels in young basketball players. In conclusion, this study showed that more strength conditioning is needed during the sport practice season. Furthermore, we also conclude that complex training is a useful working tool for coaches, innovative in this strength-training domain, equally contributing to a better time-efficient training.